Sulcal Morphology in Cingulate Cortex is Associated with Voluntary Oro-Facial Motor Control and Gestural Communication in Chimpanzees (Pan troglodytes). (14th January 2021) - Hopkins, William D; Procyk, Emmanuel; Petrides, Michael; Schapiro, Steven J; Mareno, Mary Catherine; Amiez, Celine
Abstract: Individual differences in sulcal variation within the anterior and mid-cingulate cortex of the human brain, particularly the presence or absence of a paracingulate sulcus (PCGS), are associated with various motor and cognitive processes. Recently, it has been reported that chimpanzees possess a PCGS, previously thought to be a unique feature of the human brain. Here, we examined whether individual variation in the presence or absence of a PCGS as well as the variability in the intralimbic sulcus (ILS) are associated with oro-facial motor control, handedness for manual gestures, and sex in a sample of MRI scans obtained in 225 chimpanzees. Additionally, we quantified the depth of the cingulate sulcus (CGS) along the anterior–posterior axis and tested for association with oro-facial motor control, handedness, and sex. Chimpanzees with better oro-facial motor control were more likely to have a PCGS, particularly in the left hemisphere compared to those with poorer control. Male chimpanzees with better oro-facial motor control showed increased leftward asymmetries in the depth of the anterior CGS, whereas female chimpanzees showed the opposite pattern. Significantly, more chimpanzees had an ILS in the left compared to the right hemisphere, but variability in this fold was not associated with sex, handedness, or oro-facial motor control. Finally, significant population-level leftward asymmetries were found in the anterior portion of the CGS, whereas significant rightward biases were evident in the posterior regions. The collective results suggest that the emergence of a PCGS and enhanced gyrification within the anterior and mid-cingulate gyrus may have directly or indirectly evolved in response to selection for increasing oro-facial motor control in primates.